2015
DOI: 10.1186/s13058-015-0611-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with insulin (analogues) and breast cancer risk in diabetics; a systematic review and meta-analysis of in vitro, animal and human evidence

Abstract: IntroductionSeveral studies have suggested that anti-diabetic insulin analogue treatment might increase cancer risk. The aim of this study was to review the postulated association between insulin and insulin analogue treatment and breast cancer development, and plausible mechanisms.MethodA systematic literature search was performed on breast cell-line, animal and human studies using the key words ‘insulin analogue’ and ‘breast neoplasia’ in MEDLINE at PubMed, EMBASE, and ISI Web of Science databases. A quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 79 publications
3
32
0
Order By: Relevance
“…Our null findings on risk of breast cancer in relation to LA insulin use are consistent with recent meta-analyses [36] that report possibly decreased risk or no association and run counter to others that previously received considerable attention indicating that LA insulin analogues were associated with significantly increased risk of breast cancer. In a large population-based cohort study in the Netherlands [34], users of LA insulin glargine had an increased risk of breast cancer (HR=1.58; 95% CI, 1.22-2.05) compared to users of human insulin.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our null findings on risk of breast cancer in relation to LA insulin use are consistent with recent meta-analyses [36] that report possibly decreased risk or no association and run counter to others that previously received considerable attention indicating that LA insulin analogues were associated with significantly increased risk of breast cancer. In a large population-based cohort study in the Netherlands [34], users of LA insulin glargine had an increased risk of breast cancer (HR=1.58; 95% CI, 1.22-2.05) compared to users of human insulin.…”
Section: Discussionsupporting
confidence: 84%
“…Risk of breast cancer associated with other diabetic medications is rarely studied and most results are inconclusive. Insulin glargine is associated with increased cancer risk in numerous studies [32-35] but these findings were not consistently confirmed [36], and for insulin analogues other than insulin glargine no increased risk of breast cancer has been reported. While sulfonylureas were reported to have increased risks of colorectal and pancreatic cancers in one study [15], no association was found for breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…While evidence of higher angiolymphatic invasion could be consistent with previous reports implying exogenous insulin as a growth factor for cancer cells [34], lower Ki67 is inconsistent with this postulation. Of note, since only nine patients in the cohort population were treated with insulin, the conclusions that can be drawn from this specific analysis are limited.…”
Section: Discussionsupporting
confidence: 69%
“…More specifically, a meta-analysis by Colmers et al found an increased breast cancer risk in glargine users compared to those who did not use glargine [33]. This may be attributed to the mitogenic and proliferative activity of glargine, due to its increased binding affinity to insulin-like growth factor-1 compared to human insulin [34]. However, a pooled analysis of 13 epidemiological studies did not support the association between treatment with glargine and increased incidence of breast cancer [34].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, insulin analogue stimulation increases proliferation of breast cancer cells due to enhanced IGF1R (and INSR) signaling, while exposure to human insulin showed low mitogenic potential [20]. Chronic treatment with insulin-like compounds (IGF1, insulin AspB10) with strong binding affinity towards the IGF1R, decreased the tumor latency time and showed increased MAPK-ERK signaling in a mammary gland mouse model, while insulin glargine and human insulin treatment did not significantly decrease the time for tumor development compared to the vehicle-treated mice [21].…”
Section: Introductionmentioning
confidence: 99%